The Influence of Graphitization Catalyst Electrode in Electrical Discharge Machining of Polycrystalline Diamond-Finish-ing Condition - Anugraha, Rino Andias; Rahim, M. Zulafif; Ibrahim, Rasidi (International Journal of Integrated Engineering, 2020)
Electrical Discharge Machining (EDM) is a non-contact machining process that becomes famous in machining of Polycrystalline Diamond (PCD). The material is typically used as the cutting tools for aerospace and automotive industries. However, low electrical conductivity and high melting temperature of PCD has caused slower EDM process. This investigation purposely designed to investigate the influence of different types of electrode which are Copper (ordinary electrode) and Copper-Nickel (newly proposed graphitization catalyst electrode) on EDM performance of MRR and Ra. Interestingly the newly proposed electrode gave positive impact to the investigated performance indication. Cu-Ni electrode recorded 35% better in MRR than the Cu electrode, though with higher short-circuiting rate. Cu-Ni also provided the lowest Ra value with 10% better than the best Ra produced by Cu electrode. This phenomenon occurred as due to the high interaction between the catalyst materials of nickel and diamond which supported by the qualification data provided in this investigation.